Centers needed to study women's environmental health. - Hatch, M C (2000)
The view of women as primarily fecund beings goes back to prehistory, where it is expressed in the well-known series of Venuses--stone figures of women with enlarged breasts, who are often represented as pregnant. Although the Venus figures date from the late Paleolithic era, this view of women did not change much in the next 20,000 years. With the approaching millennium, however, the field of health research has begun to consider women apart from their children or prospective progeny. Reflecting this shift in viewpoint, funds for research on the environmental health of women have now become available. However, no coordinated program has been launched on the scale of the newly established Centers for Children's Environmental Health and Disease Prevention Research (1). Should women, like children, be the focus of a concerted research effort?